Design of WWTP Anaerobic System at Tempe Factory - JAMANTO, YOGA LESTIYANTO; Anggraini, Yossi Dewi; Rizani, Mohammad Debby; Ikhwanudin, Ikhwanudin (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2024)
The tempe industry is a food industry that has the potential to pollute the environment from the liquid waste it produces. Liquid waste from the  tempe processing process if it is immediately disposed of without going through the  management process first will have an impact on environmental pollution. In Semarang City, precisely in Gunung Pati District, there is a medium-scale tempe processing factory. So far, the tempe factory's liquid waste is directly disposed of into a ditch behind  the  factory without processing the liquid waste first. This  research  is a quantitative research presented in the form of  numbers     and then explained in the form of descriptions. From the results of the wastewater quality test, the pollutant parameters BOD = 369 mg/L; COD = 28,000 mg/L; TSS  =  0.991 mg/L; and pH = 4.3. According to the Regional Regulation of the Province of Central Java Number 5 of 2012 concerning Amendments to the Regional Regulation of the Province of Central Java Number 10 of 2004, this value still does not meet the requirements. The wastewater treatment plant that the  researchers are planning is in the form of a holding tank;  Equalization Tub; Anaerobic Digesters; Gas Holder; Initial Settling Tub; Anaerobic Biofilter using bioball filter media and steel nets as a barrier for bioballs where bacteria are grown; and Final Settling Tank. With an estimated effluent from the processing of BOD, COD, and TSS of 7.47225 mg/L; 189mg/L; and 0.00669 mg/L which means it meets the quality standard. From the planning  results, it was obtained that the total budget plan for planning the tempe factory wastewater treatment plant was Rp. 111.280.021,49.